EFEK PEMANASAN LIMBAH UDANG YANG DIRENDAM DALAM AIR ABU SEKAM TERHADAP KANDUNGAN NUTRISI DAN ENERGI METABOLIS PAKAN - Mirzah Mirzah (State Islamic University of Sultan Syarif Kasim Riau, 2006)
The experiment was conducted to examine the eilect of soaking and steam heat treatment of shrimp heads waste (SHW) on nutritional quality. The objectives of this research were to determine wether the effect of the shrimp heads waste were treated in 10% of dusk rice husk solution with five level of length of steam heat (control; 0; 15; 30; 45 and 60 min) on the improvement of its the nutritive value. The feed was soaked for 48 h prior to steam heat The experiment was designed in Completely Randomized Design of 6 x 3.The results showed that there was significant effects (P < 0.05) length of steam heat to dry matter, crude protein, fat, ash contens and metabolizable energy of SHW. Increasing length of steam heat was caused reduce dry matter, crude protein, fat contens and metabolizable energy of SHW. Based on comparative cost analyses and nutritive value indicated, the best treatment was filtered of the dusk rice solution 10% and length of steam heatfor 45 min.